Molecular cloning and characterization of a calmodulin-dependent phosphodiesterase enriched in olfactory sensory neurons. - Yan, C (1995)
The sensing of an odorant by an animal must be a rapid but transient process, requiring an instant response and also a speedy termination of the signal. Previous biochemical and electrophysiological studies suggest that one or more phosphodiesterases (PDEs) may play an essential role in the rapid termination of the odorant-induced cAMP signal. Here we report the molecular cloning, expression, and characterization of a cDNA from rat olfactory epithelium that encodes a member of the calmodulin-dependent PDE family designated as PDE1C. This enzyme shows high affinity for cAMP and cGMP, having a Km for cAMP much lower than that of any other neuronal Ca2+/calmodulin-dependent PDE. The mRNA encoding this enzyme is highly enriched in olfactory epithelium and is not detected in six other tissues tested. However, RNase protection analyses indicate that other alternative splice variants related to this enzyme are expressed in several other tissues. Within the olfactory epithelium, this enzyme appears to be expressed exclusively in the sensory neurons. The high affinity for cAMP of this Ca2+/calmodulin-dependent PDE and the fact that its mRNA is highly concentrated in olfactory sensory neurons suggest an important role for it in a Ca(2+)-regulated olfactory signal termination.